Mitigation of Bad Credit in Village Credit Institutions: Customary and Good Faith Approaches to Strengthen Financial Stability - I Nyoman Sujana; Nyoman Sukandia; Anak Agung Istri Agung; Ni Nyoman Sri Puspdewi (Universitas Pendidikan Ganesha, 2025)
This community service is motivated by the economic dynamics influenced by global challenges, including the impact of the COVID-19 pandemic, which increases the risk of bad debts in Village Credit Institutions. This community service aims to examine how Village Credit Institutions (LPD) in Bali handle bad debts through the integration of customary values ​​and principles of good faith to support financial stability and build trust in the community. This type of research is a case study with a qualitative approach. The research subjects involved include LPD managers, indigenous peoples, village officials, and debtors to understand the process and results of resolving credit problems, including bad debts. Data collection methods are carried out through interviews, observations, and document studies. The data analysis method used is thematic analysis or descriptive-qualitative analysis. The analysis of the collected documents was carried out in the FGD forum. Empirical findings show that the combination of customary values ​​and good faith creates a positive image of LPD, increases customer loyalty, and strengthens LPD's position as a trusted and socially responsible financial institution. This integrated approach not only reduces the risk of bad debts but also supports sustainable growth and LPD resilience in facing economic dynamics.